Epistaxis in Children: Aetiology, Management and Outcome (Bangladesh Journal of Child Health, 2017)
Background: Although epistaxis is a common problem in preschool and school children, it is often considered as trivial and overlooked. As a result recurrent epistaxis sometimes may occur which, in some cases, may even be fatal.Objective: The present study was, undertaken to determine the etiological profile and outcome of treatment of epistaxis in children.Methods: This cross sectional study was conducted in Dhaka Shishu Hospital, Dhaka from January 2012 to December 2013. In cases of mild bleeding and stable patient, detailed history was noted along with management of the bleeding. In case of severe bleeding, history was taken after the bleeding was controlled. The diagnosis of epistaxis was based on clinical history, physical findings, laboratory investigations with examination of the nose and nasopharynx. All patients were treated conservatively initially and chemical cauterization of the specific area was considered only when conservative means failed to control the epistaxis.Results: Total 50 cases of epistoxis were enrolled. Nearly half (46%) of the patients were 3-4 years old and the rest 54% 5-6 years old with mean age being 4.6±0.9 years. Majority (68%) of the patients was male with male to female ratio being 2:1. Over twothirds (68%) of the patients were from lower middle class. All patients had anterior nasal bleeding. Seventy percent had acute epistaxis and the rest (30%) had recurrent epistaxis. Nearly half (46%) of the patients had inflammatory diseases, 28% had upper respiratory tract infections (URI), 16% had history of nasal trauma, 12% allergic rhinitis and very few patients (2%) had idiopathic causes. Eight percent patients developed shock and were resuscitated along with management of bleeding. Over one-quarter (28%) of the patients developed recurrent epistaxis and only 6% had facial oedema. All patients recovered uneventfully.Conclusion: The study concluded that the common causes of epistaxis in children in our country is inflammatory and infectious diseases of nose and upper respiratory tract and most of the epistaxis could be managed with conservative treatment alone.Bangladesh J Child Health 2015; VOL 39 (2) :73-76